Pemphigus vulgaris - Sandhya Tamgadge; Avinash Tamgadge; Daivat M Bhatt; Sudhir Bhalerao; Treville Pereira (Wolters Kluwer Medknow Publications, 2011)
Pemphigus vulgaris is a chronic autoimmune mucocutaneous disease that initially manifests in the form of intraoral lesions, which spread to other mucous membranes and the skin. The etiology of pemphigus vulgaris is still unknown, although the disease has attracted considerable interest. The pemphigus group of disease is characterized by the production of autoantibodies against intercellular substances and is thus classified as autoimmune diseases. Most patients are initially misdiagnosed and improperly treated for months or even years. Dental professionals must be sufficiently familiar with the clinical manifestations of pemphigus vulgaris to ensure early diagnosis and treatment, since this in turn determines the prognosis and course of the disease. This article presents a case report with unknown etiology along with an overview of the disease.